Issues in art and design teaching - Addison, Nicholas, 1954-; Burgess, Lesley, 1952- (Issues in subject teaching., 2003)
This book draws together a range of issues in the teaching of art and design. Building on their learning about the teaching of art and design on ITT courses, the reader is encouraged to consider and reflect to improve their judgements.